Analysis of research on communication ethics in Spain (1980-2015) - Díaz-Campo, Jesús; Segado-Boj, Francisco (Estudios sobre el Mensaje Periodístico, 2017)
This research presents the main findings of a study on communication ethics in Spanish communication scientific journals from 1980 to 2015. A total of 9.196 articles from 21 journals were analyzed, focusing on the evolution of the publication of articles on communication ethics, main topics of research and authors. Only 3,49% of the articles analyzed focused on communication ethics, although results show that the number of the articles on communication ethics is increasing. Responsibility, self regulation and justice are the most common topics